Ion-pair assisted extraction followed by 1H NMR determination of biogenic amines in food and biological matrices. (1st July 2016) - Chatzimitakos, T.; Exarchou, V.; Ordoudi, S.A.; Fiamegos, Y.; Stalikas, C.
Highlights: The extraction and determination of six biogenic amines (BAs) is presented. The polar BAs are extracted to an organic solvent using an ion pairing agent. The paired BAs are back-extracted to D2 O for 1 H NMR acquisition. The method was successfully applied to selected food and biological samples. Abstract: A selective method for the extraction and determination of six biogenic amines (BAs) by NMR is presented. Briefly, BAs are extracted into an organic solvent via the use of an ion pairing agent, followed by a back extraction in D2 O in order to acquire the 1 H NMR spectra. The method is studied with respect to the critical experimental parameters and is successfully applied to selected food substrates (dark chocolate, banana, gouda cheese) and biological samples (urine and blood plasma) signifying its potential as an alternative tool for BAs determination. Accurate and precise results are consistently achieved with all matrixes studied. The calculated limits of detection and limits of quantitation were found to be in the ranges 0.05–0.13 μg/mL and 0.14–0.38 μg/mL, respectively, for biological samples while for food samples they were in the ranges 2.25–6.25 μg/g and 6.75–18.7 μg/g, respectively.